Factors Influencing Online Shop Layout Preferences - Jach, Katarzyna; Kuliński, Marcin (Human-Computer Interaction: Users and Contexts, 2015)
The usability research on web pages layout preferences of online shops consumers has been continued since 2008 on a sample of over 1,000 Polish students. This gives a possibility to observe changes in preferences, both over time as well as across the respondents’ buying experience. Preferred locations of selected interface objects specific for an online shop, like a shopping cart, product image and search button were analyzed. The research showed that the main differentiating factor of preferences is the users’ experience. Concurrently, the layout patterns preferred by more experienced participants were consistent with standards defined as the most frequently used placement of the objects on existing online shop web pages.